2016
DOI: 10.1016/j.scitotenv.2016.09.076
|View full text |Cite
|
Sign up to set email alerts
|

Influence of commercial formulation on leaching of four pesticides through soil

Abstract: 12Studies with small soil columns (2 cm i.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…It is established that the half-life of pesticide active ingredients in soil is extended by the presence of adjuvants as has been demonstrated for chloridazon ( 50 ). A study investigating the leaching of four pesticide formulations (azoxystrobin, propyzamide, triadimenol, and cyproconazole) through a sandy loam soil found that leaching was greater than was the case with their respective active ingredients alone ( 51 ).…”
Section: Regulatory Guidance Values For Pesticides Can Be Miscalculatmentioning
confidence: 99%
“…It is established that the half-life of pesticide active ingredients in soil is extended by the presence of adjuvants as has been demonstrated for chloridazon ( 50 ). A study investigating the leaching of four pesticide formulations (azoxystrobin, propyzamide, triadimenol, and cyproconazole) through a sandy loam soil found that leaching was greater than was the case with their respective active ingredients alone ( 51 ).…”
Section: Regulatory Guidance Values For Pesticides Can Be Miscalculatmentioning
confidence: 99%
“…Effectively control weeds with few or no adverse environmental must be observed in a well-planned management system. However, the high amount of herbicides used in agronomic practices leads to the existence of contaminated groundwater sources, mainly through the leaching process [2][3][4]. The most important parameters that determine herbicide capacity to leach, and so capable to reach groundwater, are the herbicide properties, being persistence in soil and sorption the most relevant ones.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it will also be important to investigate the extent to which the effect of commercial formulation demonstrated here for propyzamide can be generalised to other compounds. We have undertaken leaching experiments with a further three pesticides to start addressing this requirement (Khan and Brown, 2016).…”
Section: Discussionmentioning
confidence: 99%